LO069: Current management of pharyngitis in the emergency department: a retrospective multicenter observational study. (2nd June 2016) - Butler, M.B.; Nason, A.; Patrick, L.; MacDonald, S.; Dong, A.X.; McIsaac, W.; Smith, D.; Gillis, J.
Abstract : Introduction: Pharyngitis is a common presenting complaint at the emergency department (ED). Historically, acute pharyngitis has been overdiagnosed as the result of a bacterial etiology, leading to over-prescription of antibiotics, and overuse of throat culturing. This study attempts to quantify the current management of acute pharyngitis in the ED, and compare to the theoretical management using a modified Centor score.Methods: This was a retrospective chart review of 1640 patients who presented to four EDs in the central zone of the Nova Scotia Health Authority that received a diagnosis of pharyngitis, bacterial pharyngitis or tonsillitis. The primary outcome was the observed rate of each diagnosis in the study population, the rate of antibiotic prescription, and the rate of throat swab cultures performed. The secondary outcomes were the rate of antibiotics and throat swabs ordered using a modified Centor score. Antibiotics as first-line treatment were indicated if the Centor score was three or greater, and throat cultures were indicated if the Centor score was two or greater.Results: A total of 1596 patients were included in the analysis. Antibiotics were given in 893 patients (0.559; 95% CI: {0.535, 0.584}). Cultures were sent on 863 patients (0.541 CI: {0.516, 0.565}). Using the modified Centor thresholds, we would have prescribed antibiotics as the first-line treatment in 77 cases (0.048 CI: {0.038, 0.060}), potentially saving 786 prescriptions, and ordered throat swabs on 502 patients (0.315, CI: {0.292, 0.338}), saving 361 cultures. The most commonly prescribed antibiotic was penicillin, and the least prescribed was metronidazole.Conclusion: Over half of patients that present with acute pharyngitis receive an antibiotic, and over half have a throat swab culture performed. Utilizing a modified Centor score would result in decreased antibiotic prescription rate, and a diminished rate of throat cultures. Incorporation of these Centor criteria could result in diminished antibiotic prescription rates for acute pharyngitis in the ED.